A field study of thermal inertia of roofs and its influence on indoor comfort. (July 2014) - D'Orazio, Marco; Di Perna, Costanzo; Di Giuseppe, Elisa
Many of the current European Member States regulations on energy saving in buildings seem to follow North European trends that call for high insulation of the envelope. However, this kind of set-up overlooks some specific elements that are necessary to build typical buildings in warmer climates. Thermal inertia on the internal surface of the envelope has traditionally been used in such contexts not only to contain solar gains but also to protect against cold winter because of its capacity to store and to slowly release energy. This research investigates how thermal inertia on roof slabs could positively affect the comfort indoors, also in buildings that tend towards being nearly zero-energy buildings, as suggested by last European Directive 2010/31/EU. With this aim, an experiment was conducted on a full-scale building with different roofs, on light and heavy slabs, under hot and moderate climatic conditions (Ancona, Italy). The thermal performance of roofs was monitored during summer and winter seasons. In winter, the building was also subjected to cyclical internal heat gains. The experiment demonstrated that a certain thermal inertia in the slab guarantees better indoor comfort in both summer and winter, and it can also reduce energy consumption from heating.